Complementation of the cs dis2-11 cell cycle mutant of Schizosaccharomyces pombe by a protein phosphatase from Arabidopsis thaliana. - Nitschke, K (1992)
The activities of type I protein phosphatases play a central role in eukaryotic cell cycle control. Here, we report the cloning and characterization from the flowering plant Arabidopsis thaliana of a cDNA clone named PP1-At which is highly homologous to protein phosphatase 1. The deduced amino acid sequence of PP1-At shows that the PP1-At protein is 318 amino acid residues long and has a molecular weight of 35,298 Da. The PP1-At protein has strong similarity to all other known protein phosphatase type 1 catalytic subunits. Approximately 62% of the amino acids are identical to type 1 protein phosphatases of rabbit, mouse, Saccharomyces cerevisiae and Schizosaccharomyces pombe. RNA blot analysis revealed a single mRNA species of approximately the same size as the cDNA isolated. The PP1-At-encoded mRNA of 1.3 kb is abundant in most vegetative Arabidopsis tissues, with the lowest level of expression in leaves. When transferred to the fission yeast S.pombe, the PP1-At-encoded protein can rescue a semidominant mutant, cold sensitive (cs) dis2-11, which under nonpermissive conditions is unable to complete chromosome disjunction.